NAVIGATING MARKET FLUCTUATIONS: INTEREST RATES AS A MODERATOR IN THE FINANCIAL PERFORMANCE–STOCK PRICE EQUATION - Jamian Purba; Shafa Amelia Putri; Dian Sulistyorini Wulandari (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the influence of financial performance on stock prices with interest rates as a moderating variable. Using panel data from publicly listed companies between 2018 and 2023, a random effects model was employed based on Chow, Hausman, and the LM test results. The findings show that financial performance has a positive and significant effect on stock price. Moreover, the interaction term between financial performance and interest rates indicates a negative moderating effect, suggesting that higher interest rates weaken the impact of financial performance on stock prices. These results underline the importance of considering macroeconomic variables in investment evaluations and corporate decision-making.